Jurnalistik Online Indonesia: Analisis Framing Tiga Portal Berita Online di Indonesia - Mahfud Anshori (Jurnal Komunikasi, 2011)
Journalism has its own problems: declining of revenue from circulations and advertisement; lacking of reading-less audience and authority. Most media institutions seek a new strategy to keep up their business, including convergence their products, institutions, and use the communication technology to serve their audience. Unfortunately, convergence in online news is not enough to solve the problems. Media routines, multimedia skill, and other technical barriers in news productions are more problematic rather than to bring up the news on the net. This research focuses on the media frames on online news, or in other word, how online news being constructed and influenced by culture of production from the media itself. Three online media were analyzed using Teun Van Dijk's framing model and confronted with contextualized journalism as primary element of online journalism.